Chronic Obstructive Pulmonary Disease: evidence for and autoimmune component. - WALSH, PATRICK (My University, 2009)
Chronic obstructive pulmonary disease (COPD) is characterized by an irreversible limitation on pulmonary airflow associated with chronic inflammation and mucous hypersecretion (chronic bronchitis) and/or the pathological destruction of alveolar airspaces leading to emphysema. COPD, predominantly as a result of tobacco smoke exposure, represents the fourth leading cause of mortality worldwide and its prevalence is increasing. Despite this, much of the basic mechanisms which contribute to disease progression remain to be elucidated and current therapeutic approaches are, for the most part, based upon alleviating patient symptoms (bronchodilators) as opposed to treating the underlying pathological mechanisms triggered in response to cigarette smoke exposure. The classic disease paradigm suggests that an imbalance of pulmonary matrix proteases versus anti-proteases underlies the tissue destruction and inflammation associated with COPD. However, there is a growing appreciation of the complex and multifaceted nature of the pathological mechanisms associated with disease progression. Recently, there has been mounting evidence indicating that COPD patients exhibit many of the characteristics of a classical autoimmune response. We will discuss current evidence in support of this paradigm and outline how future therapeutic approaches may be tailored to address this. Cellular & Molecular Immunology. 2009;6(2):81-86
PUBLISHED
Keywords: COPD; Autoimmunity; Emphysema; Th1; Th17; Immunology, Inflammation & Infection